2012
DOI: 10.1016/j.jacc.2011.10.880
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic Acid in Patients With Chronic Heart Failure

Abstract: UDCA is well tolerated in patients with CHF. UDCA improves peripheral blood flow and is associated with improved markers of liver function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Furthermore, alterations of BA metabolism have been found in cardiac disease and heart failure [30, 31, 53]. Recently, G-protein-coupled BA receptor-1 has been identified as central pathway in BA-mediated hemodynamic alterations [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, alterations of BA metabolism have been found in cardiac disease and heart failure [30, 31, 53]. Recently, G-protein-coupled BA receptor-1 has been identified as central pathway in BA-mediated hemodynamic alterations [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 6 weeks’ UDCA therapy was found to improve endothelium-dependent vasodilatation and arterial blood flow in patients with CHF under conditions of impaired nitric oxide production (91). In addition, a randomized, placebo-controlled clinical trial demonstrated that UDCA significantly improved peak post-ischemic blood flow in the arm (105). It will be important to find out if increased endothelial DDAH1 expression and/or reduction of ADMA levels played a role in the beneficial effects of UDCA observed in these clinical studies.…”
Section: Regulation Of Ddah1 Expression By Farnesoid X Receptors (Fxrmentioning
confidence: 99%
“…It should be noted, however, that treatment with UDCA can only alleviate some of the symptoms in the early stages of the disease, not cure it. Interestingly, current studies are under way to test the effects of UDCA in cardiovascular disease [55], which lends further credibility to Turi’s suggested use of the compound.…”
Section: Discussionmentioning
confidence: 86%